Presumed Isotretinoin-Induced, Concomitant Autoimmune Thyroid Disease and Ocular Myasthenia Gravis: A Case Report - Huseyin Gursoy; Idil Cakmak; Nilgun Yildirim; Hikmet Basmak (Karger Publishers, 2012)
Introduction: There are many adverse effects that have been described for isotretinoin. To the best of our knowledge, this is the first report of a possible association of oral isotretinoin intake with autoimmune thyroiditis and ocular myasthenia gravis (OMG). Case Presentation: A 19-year-old Caucasian male, who had used oral isotretinoin for severe acne disease for the previous six months, was referred to our clinic. He had a three-week history of diplopia and variable bilateral ptosis. Physical examination showed moderate periorbital edema and limitations of up- and down-gaze in the left eye. Laboratory findings and thyroid ultrasound were consistent with autoimmune thyroiditis. Antithyroid therapy did not relieve the clinical symptoms. Concomitant OMG was suspected. Variable ptosis and a positive response to oral prednisolone of 40 mg/day and pyridostigmine of 360 mg/day supported the diagnosis of concomitant autoimmune thyroiditis and OMG. Conclusion: Autoimmune disorders may be triggered by oral isotretinoin treatment. Clinicians prescribing isotretinoin should be aware of the possible association between isotretinoin intake and concomitant autoimmune thyroiditis and OMG.